WAYS TO IMPROVE THE CONSTRUCTION OF CLEANING COTTON FROM HEAVY MIXTURES (American Journal of Interdisciplinary Research and Development, 2023)
The article examines the advantages and disadvantages of the existing options of the ginning equipment used in cotton processing in cotton ginning enterprises. In order to eliminate the shortcomings, a new construction of the stone crusher was proposed, and it was achieved to increase its efficiency.